Anti-obesity Effects of Erythrina Abyssinica Stem Bark Extract in Flies Exposed to a High Fat Diet - Asiimwe, Oscar Hilary; Wampande, Eddie; Rubaihayo, John; Kasozi, Keneth Iceland; Kinyi, Hellen Wambui (Heliyon, 2022)
An in vitro assay on Sigmoidin A from Erythrina abyssinica stem bark revealed its potency to inhibit pancreatic lipase. However, studies indicate activity of extract bioactive compounds in combination far exceed the favorable effects of each individual compound due to synergy and additive effects. In this study, we provide information on the effect of E. abyssinica stem bark extract in Drosophila melanogaster. The objective of the study was to determine the safety and effects of E. abyssinica stem bark extract on fly survival, body weight, triglycerides, sterol, total protein, and catalase activity of obese male D. melanogaster.
Keywords: Erythrina abyssinica; Obesity; Triglycerides; Catalase; Drosophila melanogaster